Female Nurses’ Knowledge and Practices in Early Breast Cancer Detection at Primary Health Care Clinics - helal , Ali; Alsaif , Zainab Yasser; Albayyabi, Zahra Abdullah; Alharbi, Omar Mohammed; Alhuthali , Ozouf Mohammed Salem; Alshamrani, Rahmah Ali; Hazazi , Farah; AL-Maskeen, Zainab Tawfiq; Almuntashiri , Abdulkhaliq Hajer; Alqahtani , Saad Mohammed; Alsaadi, Matr Musleh; Sayer , Seham Salem; et al. (Journal of Ecohumanism, 2024)
Background: Breast cancer remains a leading cause of morbidity and mortality among women worldwide, with early detection being critical for improving treatment outcomes. Female nurses in primary health care clinics play a pivotal role in early breast cancer detection through patient education, clinical examinations, and referrals. However, gaps in knowledge and practice among nurses can hinder these efforts. This study aimed to assess the knowledge and practices of female nurses regarding early breast cancer detection in primary health care settings. Methods: A descriptive cross-sectional study was conducted among 100 registered female nurses from primary health care clinics. Data were collected using a structured, self-administered questionnaire validated by experts. The questionnaire covered demographic information, knowledge of breast cancer risk factors and screening methods, and self-reported practices related to early detection. Descriptive and inferential statistics were used to analyze the data, with a p-value < 0.05 considered statistically significant. Results: The majority of nurses demonstrated good knowledge of breast cancer risk factors (80% identified family history) and symptoms (93.3% recognized lumps). However, only 66.7% knew the correct frequency for breast self-examination (BSE). In practice, 63.3% performed clinical breast examinations regularly, while 60% educated patients about BSE. Notably, 86.7% expressed interest in additional training. Nurses with prior training exhibited significantly higher knowledge and practice scores (p < 0.05). Conclusion: While female nurses in primary health care clinics possess satisfactory knowledge about early breast cancer detection, their practices are inconsistent, highlighting a gap between knowledge and application. Barriers such as insufficient training and institutional support need addressing. Continuous professional development and targeted interventions are recommended to enhance nurses’ roles in early detection and improve breast cancer outcomes.